Posterior pericardiotomy in heart valve surgery; is it still performed or neglected? - Mubarak, Yasser (Journal of Cardiology and Cardiovascular Medicine, 2022)
Background: Posterior pericardiotomy (PP) is helpful to prevent arrhythmia; especially atrial fibrillation (AF), and cardiac tamponade postoperative cardiac valve surgery. The incidence of postoperative AF is increased due to postoperative pericardial effusion (PE). This study aimed to investigate the early outcome of PP after heart valve surgery. Methods: In this prospective study, 120 patients underwent elective valve heart surgery at our center from January 2020 until April 2022. Patients were followed up for AF and pericardial effusion, and reopening due to tamponade. Results: The mean age of patients was 35.26 years, 70.2% were female and 29.8% were male. Surgery was elective and all were valve surgery. The incidence of postoperative AF was 2%, and pericardial effusion was seen in 1% of patients. Tamponade was not seen in any case. Left PE needed intervention tube drainage of 2%. Conclusion: Posterior pericardiotomy is a simple and safe procedure during valve heart surgery, and it is effective in reducing the incidence of atrial fibrillation, pericardial effusion, and tamponade.